The Impact of Financial Literacy and Fintech on the Financial Behavior of Cirebon Economics Students - Henni Herdiyani; Kamalah Saadah (Value : Jurnal Manajemen dan Akuntansi, 2026)
This study focuses on analyzing the role of financial literacy as a moderator in mitigating the risk of consumptive behavior and unhealthy financial management due to the use  of financial technology (fintech) among students, The purpose of this study is to find out the extent of the influence of financial literacy and the influence of financial technology on students' financial behavior. The population of this study is economics students in Cirebon, while the research sample is economics students who use financial technology on a daily basis. Data collection was carried out through the distribution of questionnaires. Hypothesis testing was carried out through multiple linear regression analysis as well as suitability and significance tests.